2022
DOI: 10.3390/ijerph191711001
|View full text |Cite
|
Sign up to set email alerts
|

Service User and Carer Views and Expectations of Mental Health Nurses: A Systematic Review

Abstract: Service users’ views and expectations of mental health nurses in a UK context were previously reviewed in 2008. The aim of this systematic review is to extend previous research by reviewing international research and work published after the original review. Five databases were searched for studies of any design, published since 2008, that addressed service user and carer views and expectations of mental health nurses. Two reviewers independently completed title and abstract, full-text screening and data extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…This may promote a more collaborative approach to their care and ensure that their narrative is shared and captured in any resulting care planning. This collaborative approach, and the potential for increased understanding and compassion from mental health staff as demonstrated in this study, may facilitate a more positive therapeutic relationship between service users and their team; something which has been highlighted as critical in impacting service user experiences of mental health nursing (Moyo et al, 2022).…”
Section: Limitations and Research Implicationsmentioning
confidence: 86%
“…This may promote a more collaborative approach to their care and ensure that their narrative is shared and captured in any resulting care planning. This collaborative approach, and the potential for increased understanding and compassion from mental health staff as demonstrated in this study, may facilitate a more positive therapeutic relationship between service users and their team; something which has been highlighted as critical in impacting service user experiences of mental health nursing (Moyo et al, 2022).…”
Section: Limitations and Research Implicationsmentioning
confidence: 86%
“…This study had one important limitation related to the fact that all the participants had mental health disorders only of the psychotic spectrum. Notwithstanding this limitation, it is essential to understand which factors represent a good therapeutic relationship with the nurse from the perspective of patients with mental health disorder within the psychotic spectrum so that it can be improved and targeted [ 62 , 63 ]. However, future studies should consider patients with mental health disorders of a different spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…However, they often report encountering negative attitudes and discrimination from mental health staff (61,62). Similarly, previous reports have shown that carers' views are also rarely solicited by mental health professionals or considered during decision making (11,63).…”
Section: Shortcomings In the Delivery Of Carementioning
confidence: 98%